Freshwater wetland–driven variation in sulfur isotope compositions: Implications for human paleodiet and ecological research - Guiry, Eric J.; Orchard, Trevor J.; Needs-Howarth, Suzanne; Szpak, Paul (Frontiers in Ecology and Evolution, 2022)
Sulfur isotope (δ34S) analyses are an important archaeological and ecological tool for understanding human and animal migration and diet, but δ34S can be difficult to interpret, particularly in archaeological human-mobility studies, when measured isotope compositions are strongly 34S-depleted relative to regional baselines. Sulfides, which have distinctively low δ34S, are potentially key for understanding this but are often overlooked in studies of vertebrate δ34S. We analyse an ecologically wide range of archaeological taxa to build an interpretive framework for understanding the impact of sulfide-influenced δ34S on vertebrate consumers. Results provide the first demonstration that δ34S of higher-level consumers can be heavily impacted by freshwater wetland resource use. This source of δ34S variation is significant because it is linked to a globally distributed habitat and occurs at the bottom of the δ34S spectrum, which, for archaeologists, is primarily used for assessing human mobility. Our findings have significant implications for rethinking traditional interpretive frameworks of human mobility and diet, and for exploring the historical ecology of past freshwater wetland ecosystems. Given the tremendous importance of wetlands’ ecosystem services today, such insights on the structure and human dynamics of past wetlands could be valuable for guiding restoration work.